Fundus tessellation: prevalence and associated factors : the Beijing Eye Study 2011 - Yan, Yan Ni; Jonas, Jost B. (Ophthalmology, 2015)
Purpose: To examine the prevalence of fundus tessellation and its associated factors. Design: Population-based study. Participants: The Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6±9.8 years (range, 50-93 years). Methods: Participants underwent a comprehensive ophthalmic examination. By using 45° color fundus photographs of the macula and optic disc, fundus tessellation, defined as variation in the visibility of the large choroidal vessels, was differentiated into 3 grades. Main Outcome Measures: Fundus tessellation. Results: Assessment of fundus tessellation was available for 3442 individuals (99.6%) or 6789 eyes (98.6%). In multivariate analysis, a higher degree of fundus tessellation (mean, 0.84±0.79) was associated with older age (P < 0.001; standardized correlation coefficient beta, 0.14), male sex (P < 0.001; beta, −0.08), lower body mass index (P = 0.04; beta, 0.03), worse best-corrected visual acuity (P < 0.001; beta, 0.05), thinner subfoveal choroidal thickness (P < 0.001; beta, -0.51), longer axial length (P < 0.001; beta, 0.11), larger parapapillary beta zone (P < 0.001; beta, 0.08), lower prevalence of intermediate age-related macular degeneration (AMD) (P = 0.02; beta, -0.04), and lower prevalence of late AMD (P = 0.007; beta, -0.04). If parapapillary beta zone was dropped, higher glaucoma prevalence (P = 0.003) was associated with a higher degree of fundus tessellation. Prevalence of diabetes mellitus and retinal vein occlusions, mean blood pressure, and intraocular pressure were not (P > 0.10) associated with fundus tessellation. In a reverse manner, thinner subfoveal choroidal thickness was associated with a higher degree of fundus tessellation (P < 0.001; beta, -0.49) in the multivariate analysis. Subfoveal choroidal thickness decreased from 322±90 μm (95% confidence interval [CI], 317-327) in eyes without fundus tessellation to 229±80 μm in eyes with grade 1, to 122±52 μm in eyes with grade 2, and to 81±37 μm in eyes with grade 3 of fundus tessellation. Conclusions: Fundus tessellation is a surrogate for choroidal thinness and may be a clinical sign for a leptochoroid. After adjusting for ocular and systemic parameters, fundus tessellation also is associated with a larger parapapillary beta zone and higher glaucoma prevalence, and a lower prevalence of intermediate and late AMD. Its association with lower visual acuity warrants further investigation.